The Impact of the Global Crisison South-Eastern Europe - Spadafora, Francesco (IMF Working Papers; Working Paper ;, 2011)
This paper analyzes the impact of the global crisis on six South-Eastern European countries. The main objective is to compare macro-financial conditions and policies in the run-up to the crisis as well as to compare the policy responses to it, so as to highlight, inter alia, possible country-specific constraints. While sharing a common pre-crisis pattern of strong capital inflows and robust growth, a key difference in the conduct of macroeconomicpolicies is that some countries adopted expansionary (and procyclical) fiscal policies. These moves exacerbated external vulnerabilities and compromised the ability to discretionarily use the fiscal instrument in acountercyclical fashion.